Autonomous Aerial Ice Observation for Ice Defense - Haugen, Joakim; Imsland, Lars Struen (Modeling, Identification and Control: A Norwegian Research Bulletin, 2014)
One of the tasks in ice defense is to gather information about the surrounding ice environment using various sensor platforms. In this manuscript we identify two monitoring tasks known in literature, namely dynamic coverage and target tracking, and motivate how these tasks are relevant in ice defense using RPAS. An optimization-based path planning concept is outlined for solving these tasks. A path planner for the target tracking problem is elaborated in more detail and a hybrid experiment, which consists of both a real fixed-wing aircraft and simulated objects, is included to show the applicability of the proposed framework. (c) 2014 Norwegian Society of Automatic Control. Creative Commons Attribution 3.0 Unported (CC BY 3.0) license. See: http://creativecommons.org/licenses/by/3.0/.